Analyzing Intercultural Communicative Competence in Grade Eleven English Textbook - Joshi, Dev Ram (KMC Journal, 2025)
This study aims to explore the cultural contents and activities in the English textbook of grade eleven to identify how the textbook can contribute to the development of intercultural communicative competence (ICC) in secondary level students of Nepal. I selected this book purposefully for data collection to find the answers of my research questions about the cultural contents presented in the book and their potential to enhance ICC in English language learners from school level. Similarly, I analyzed the contents through the qualitative content analysis method collecting data from the book by following the framework of Byram’s ICC Model, Kramsch’s cultural perspective, and Cortazzi and Jin’s sources of cultures. I found extensive inclusion of target and international cultural contents in the textbook which can ensure the open space to practise and foster the intercultural communicative activities. Additionally, the match of cultural contents with Byram’s ICC model and Cortazzi & Jin’s sources of culture indicate the potentiality of textbook to enhance ICC in students. This study can be useful for the English language teachers and learners guiding them how this textbook can contribute to develop intercultural communicative competence.